PEACEBUILDING AND CONFLICT TRANSFORMATION – STRATEGIC ASPECTS - Dimitriev Emil; Pavleski Aleksandar (Филозофски факултет, 2023)
Abstract: Today, in the 21st century, we can still talk about countries and regions around the world, with weak, unproductive and highly corrupt governing systems, with “social” systems in which basic human freedoms and rights are not respected, with weak or destroyed economies, with uncontrolled poverty, etc. Failed states provide ideal grounds for emergence and development of civil strife, criminality, and other updated or new security risks and threats that in general target civilians and commit massive human rights violations. On the one hand, such “updated”, redesigned and new security risks and threats easily extend beyond national borders, while on the other hand, the capacity of the International community for successfully intervening and dealing with them behind the borders, remains questionable. In this regard, the paper analyses perhaps the most promoted instruments of the International community on this plan in the past 30 years, i.e. peace building and conflict transformation. In fact, paper aims to identify what is distinctive about strategic aspects of the peacebuilding and conflict transformation as well as to identify their key dimensions. The paper does agree that such approaches and mechanisms need to be continually adjusted in response to the changing nature of threats, risks and conflicts, as well as that current theories must be adapted in order to take proper account of the globalization of conflicts and conflict interventions. Moreover, the paper highlights the need for a strategic approach of peacebuilding and conflict transformation that would consider both the factors that promote peacebuilding and those that exacerbate conflict at these different levels over an extended period of time from before the outbreak of violent conflict to well after its resolution.
Keywords: peacebuilding, conflict-transformation, International community, peace, conflict